Pengembangan bahan ajar berbantuan geogebra pada materi transformasi geometri - Siti Masliah; Heris Hendriana; Ratni Purwasih (IKIP Siliwangi, 2023)
By conducting this research, it aims to develop teaching materials in the form of geogebra-assisted worksheets that are practical and suitable for use as a medium for learning mathematics. The research method used was R&D with the ADDIE model which consisted of five stages, namely Analysis, Design, Development, Implementation, and Evaluation which were carried out at SMKS Mandala Putra 2. The sample for this study was 10 class XII students as a small-scale trial and class XI students as many as 30 people as a large-scale trial. Consisting of media experts, material experts and math teachers as validators in this study. The data collection technique is by distributing response questionnaires to students, then the results are calculated using Microsoft Excel. Based on the results of the research that has been done, the product developed received validation from media experts at 94.7%, from material experts at 74.3%, and from math teachers at 73.3%, so it is included in the very valid category. Products that have been validated are then tested on students on a small scale with a result of 78% and on a large scale with a result of 80%, so that it is included in the practical category.